Highway engineering - Wright, Paul H.; Dixon, Karen (Hoboken, New Jersey : John Wiley & Son, Inc., 2003)
The book present the broad field of highway engineering as it currently practices and is likely to be several years to come. It also includes materials of emerging significance.
Contents Introduction Highway administration Transportation planning Highway evaluation Driver, pedestrian, and vehicle charateristics Traffic characteristics Geometric design og highways Roadside design Intesections, Interchanges, and parking facilities Highway mass transit facilities Traffic engineering Drainage and drainage structures Surveys, plans, and estimates Contracts and supervision Highway materials Flexible pavement design Earthwork operations and equipment Bases, subbases, and low-cost surfaces High-type bituminous pavements Concrete pavements Highway maintenance and rehabilitation Appendix Index
Includes bibliographical references.
Keywords: HIGHWAY ENGINEERING